How to Do Systems Analysis Primer and Casebook. - Gibson, John E. (New York Academy of Sciences Ser., 2016)
Presents the foundational systemic thinking needed to conceive systems that address complex socio-technical problems This book emphasizes the underlying systems analysis components and associated thought processes. The authors describe an approach that is appropriate for complex systems in diverse disciplines complemented by a case-based pedagogy for teaching systems analysis that includes numerous cases that can be used to teach both the art and methods of systems analysis.-Covers the six major phases of systems analysis, as well as goal development, the index of performance, evaluating candidate solutions, managing systems teams, project management, and more -Presents the core concepts of a general systems analysis methodology -Introduces, motivates, and illustrates the case pedagogy as a means of teaching and practicing systems analysis concepts -Provides numerous cases that challenge readers to practice systems thinking and the systems methodology How to Do Systems Analysis: Primer and Casebook is a reference for professionals in all fields that need systems analysis, such as telecommunications, transportation, business consulting, financial services, and healthcare. This book also serves as a textbook for undergraduate and graduate students in systems analysis courses in business schools, engineering schools, policy programs, and any course that promotes systems thinking. -- Provided by publisher.